FKBP5-CCL5 interaction promotes neuroinflammation and neuronal apoptosis in ischemic stroke by regulating the MAPK pathway and enhancing NET formation - Li, Zhongchen; Yin, Tengkun; Guo, Hongyang; Liu, Zhenxing; Wang, Peijian; Liu, Chao; Wang, Qingbo; Zhang, Meng; Xiao, Yilei; Wang, Jiyue; Hao, Jiheng; Zhang, Liyong (Frontiers in Immunology, 2025)
BackgroundThe pathophysiology of ischemic stroke is not fully elucidated. Upregulation of FKBP5 in brain ischemia/reperfusion injury has been found to be associated with the severity of ischemic and reperfusion damage. However, its specific role in ischemic stroke progression remains unclear.MethodsA total of 40 ischemic stroke patients and 40 age- and sex-matched healthy donors (HDs) were enrolled in this work to evaluate the expression of FKBP5, the formation of neutrophil extracellular trap (NET), and the correlation between NET and stroke. Moreover, transient middle cerebral artery occlusion (tMCAO) mouse model with 60 min occlusion (n = 15/group) was treated with CI-amidine to demonstrate the effect of NET on the stroke-related brain injury. Primary neurons were isolated from mouse brain tissue to evaluated the effect of NET on neuronal apoptosis through flow cytometry the TUNEL assays. In addition, BV2 microglial cells were transfected with FKBP5 overexpression and knockdown vectors. The microglial cells polarization, neutrophil NETs formation, and the underlying molecular action mechanism were measured. For specific methods: detected the levels of H3cit, MPO-DNA, IL-1β, IL-10, TNFα, and iNOS by ELISA; Pathological staining was viewed for the neuronal morphological changes; flow cytometry and TUNEL staining were viewed for the neuronal cell apoptosis; detected the protein levels of FKBP5, CD206, CCL5, and MAPK pathway by western blot.ResultsIn this study, we observed significant upregulation of FKBP5 in ischemic stroke patients, which was associated with increased expression of NET markers, such as H3cit and MPO-DNA complexes. This upregulation correlated with stroke severity and outcomes. In a transient middle cerebral artery occlusion (tMCAO) mouse model, treatment with the NET inhibitor CI-amidine significantly reduced brain injury, infarct size, and NET marker levels, suggesting therapeutic potential in targeting NETs. We further found that FKBP5 modulates microglial polarization towards a pro-inflammatory M1 phenotype and promotes NET formation. FKBP5 interacts with CCL5, enhancing MAPK pathway activation and increasing pro-inflammatory cytokine production, including TNF-α and IL-1β. Intervention with the MAPK pathway inhibitor AZD6244 effectively inhibited these effects.ConclusionsThe current findings suggest that FKBP5 might modulate CCL5-mediate p38 MAPK signaling and NET formation, thereby contributing to post-stroke neuroinflammation and neuronal apoptosis. Further prospective research is needed to verify the potential of FKBP5 as therapeutic targets for ischemic stroke treatment.